2015
DOI: 10.5194/sed-7-1577-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Land use effects on soil organic carbon sequestration in calcareous leptosols in former pastureland – a case study from the Tatra Mountains (Poland)

Abstract: Abstract. The purpose of the paper is to show SOC sequestration rates in calcareous shallow soils in reforested areas in Tatra Mts. with a particular focus on the different forms of organic matter (OM) storage. Three plant communities creating a mosaic on the slopes of the valley were taken into account. After 50 years since the conversion of pastureland to grassland, dwarf pine shrub, and larch forest on soils, the development of genetic soil horizons as well as SOC sequestration in soil occur despite the st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 64 publications
0
21
0
1
Order By: Relevance
“…The top layer of the permafrost un− dergoes thawing, and the thickness of the active layer changes as the weather con− ditions change. Studies of the physical properties of permafrost, including its ac− Introduction Soils of boreal and polar environments now has been considered as key components of global carbon cycle Bruun et al 2015;Peng et al 2015;Wasak and Drewnik 2015;Szymański et al 2016). This is especially important for Arctic soils, because they contain maximum stocks of soil organic matter (SOM) within the whole pedosphere (McGuire et al 2009;Oliva et al 2014;Zubrzycki et al 2014;Fritz et al 2015;Ping et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The top layer of the permafrost un− dergoes thawing, and the thickness of the active layer changes as the weather con− ditions change. Studies of the physical properties of permafrost, including its ac− Introduction Soils of boreal and polar environments now has been considered as key components of global carbon cycle Bruun et al 2015;Peng et al 2015;Wasak and Drewnik 2015;Szymański et al 2016). This is especially important for Arctic soils, because they contain maximum stocks of soil organic matter (SOM) within the whole pedosphere (McGuire et al 2009;Oliva et al 2014;Zubrzycki et al 2014;Fritz et al 2015;Ping et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Higher content of organic matter was observed in soils developed from weathered rocks rich in calcium carbonate than in other soils under comparable climate conditions with the same vegetation and land use (among others Dobrzañski and Turski 1972, KuŸnicki and Sk³odowski 1973, Niemyska-£ukaszuk 1977a, Duchaufour 1982, Shang and Tiessen 2003, Ahmed et al 2012, Wasak and Drewnik 2015, Yang et al 2016, Wasak 2017. In research covering more than 1800 soil profiles from the entire territory of Germany, Grüneberg et al (2014) confirmed the higher content of organic matter in soil rich in carbonates both for plains and uplands, and for mountainous areas (Table 1).…”
Section: Introductionmentioning
confidence: 90%
“…On the other hand, grazing brought also a positive impact on slopes: due to manuring related to the paddock grazing system the soils were enriched in biogenic components, and plant nutrients were better balanced (Skiba and Zawilińska, 1990). In fifty years since the conversion of pastureland into grasslands and forest, the development of genetic soil horizons occurs in eroded calcareous soils (Wasak and Drewnik, 2015).…”
Section: Influence Of Grazing On Landform and Soils Transformationmentioning
confidence: 99%